Les « salles à auges » Des édifices controversés de l'Antiquité tardive entre Afrique et Proche-Orient - Rocca, Elsa; Piraud-Fournet, Pauline; Baratte, François (Collection de la Casa de Velázquez, 2022)
It is exceptional in archaeology to find buildings with a complex and organized plan, built with care, but whose use still escapes us: this is however the case in Roman Africa of the late group of «trough monuments», which had to be designated by one of their structural characteristics, for lack of knowledge of their function. Their stone troughs, widely used in the Roman world, offered multiple possibilities: they are commonplace in the Near East in stables or cowsheds. The contributions gathered in this volume, exploring various Mediterranean regions, review the different contexts in which these elements appear -rural, commercial or linked to the distribution of foodstuffs by the State or the Church- and suggest several hypotheses of interpretation.